2012
DOI: 10.4161/gmcr.19512
|View full text |Cite
|
Sign up to set email alerts
|

Surveying of pollen-mediated crop-to-crop gene flow from a wheat field trial as a biosafety measure

Abstract: Outcrosses from genetically modified (GM) to conventional crops by pollen-mediated gene flow (PMGF) are a concern when growing GM crops close to non-GM fields. This also applies to the experimental releases of GM plants in field trials. Therefore, biosafety measures such as isolation distances and surveying of PMGF are required by the regulatory authorities in Switzerland. For two and three years, respectively, we monitored crop-to-crop PMGF from GM wheat field trials in two locations in Switzerland. The polle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 39 publications
(27 reference statements)
2
10
0
Order By: Relevance
“…3) and phenotypic data (Table 3) did not reveal any escapes among the seedlings survived after the herbicide treatment. Those data showed that the method of screening for herbicide-resistant hybrids applied in the present study was much more reliable than those used in the previous experiments (Messeguer et al 2004;Gatford et al 2006;Foetzki et al 2012).…”
Section: Discussionsupporting
confidence: 51%
See 4 more Smart Citations
“…3) and phenotypic data (Table 3) did not reveal any escapes among the seedlings survived after the herbicide treatment. Those data showed that the method of screening for herbicide-resistant hybrids applied in the present study was much more reliable than those used in the previous experiments (Messeguer et al 2004;Gatford et al 2006;Foetzki et al 2012).…”
Section: Discussionsupporting
confidence: 51%
“…Gatford et al (2006) reported only one transgenic hybrid out of 58 seedlings that survived the spraying with 0,3 % Basta (15 mg/L PPT). The most of 900 survived wheat seedling found by Foetzki et al (2012) during several years of field trials by application of the similar herbicide concentration (10 mg/L PPT) were also false-positive. Messeguer et al (2004) reported the same problem of transgenic hybrids identification among herbicide resistant seedlings in rice transgene flow experiment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations